Relação entre disfunções cervicais e desordens no complexo articular temporomandibular - Engelman, Thais Lazzarotto; Ludwig, Vanessa Luana (My University, 2024)
Introduction: Temporomandibular disorder (TMD) is a set of functional changes, that affect the masticatory and stomatognathic systems, involving the temporomandibular joint complex and adjacent structures. The prevalence of cervical and temporomandibular dysfunctions has been increasing, negatively impacting quality of life. Objective: To evaluate the presence of symptoms related to temporomandibular joint disorders in individuals diagnosed with cervical dysfunctions. Methodology: This is an observational, descriptive, quantitative and cross-sectional study, composed of 25 individuals with cervical dysfunctions. Data were collected through the application of questionnaires containing personal data, clinical diagnosis, lifestyle habits, and also the Fonseca Anamnestic Index. Data analyzes were performed by descriptive statistics, with mean, standard deviation, absolute frequency and relative frequency. Data crossing was performed using the Chi-square test, with a significance level set at P < 0.05. Results: The prevalence of TMD symptoms was found in 96% of participants, with 36% having mild TMD, 32% having moderate TMD, 28% having severe TMD and 4% having no TMD. Of these results, 68% were female and 32% were male, 40% did not exercise, 16% were smokers and 36% were alcoholics. However, the Chi-square test did not show statistical significance between genders, lifestyle habits and degrees of involvement. Conclusion: The study demonstrated a high prevalence of TMD symptoms in individuals with cervical dysfunctions. The evidence presented serves as a starting point for encouraging new research on the subject, offering insights into epidemiological knowledge. [resumo fornecido pelos autores]
Introdução: A disfunção temporomandibular (DTM) é um conjunto de alterações funcionais, que afetam os sistemas mastigatórios e estomatognáticos, envolvendo o complexo da articulação temporomandibular e estruturas adjacentes. A prevalência das disfunções cervicais e temporomandibulares tem aumentado, impactando negativamente na qualidade de vida. Objetivo: Avaliar a presença de sintomas relacionados a desordens no complexo articular temporomandibular em indivíduos diagnosticados com disfunções cervicais. Metodologia: Trata-se de uma pesquisa observacional, descritiva, quantitativa e de corte transversal, composta por 25 indivíduos com disfunções cervicais. Os dados foram coletados através da aplicação de questionários contendo dados pessoais, diagnóstico clínico, hábitos de vida e, também, o Índice Anamnésico de Fonseca. As análises dos dados foram feitas por estatística descritiva, com média, desvio padrão, frequência absoluta e frequência relativa. Os cruzamentos de dados foram realizados através do Teste Qui-quadrado, com nível de significância estabelecido em p<0,05. Resultados: A prevalência de sintomatologias de DTM foi encontrada em 96% dos participantes, sendo 36% com DTM leve, 32% com DTM moderada, 28% com DTM severa e 4% sem DTM. Destes resultados, 68% eram do gênero feminino e 32% do gênero masculino, 40% não praticavam exercício físico, 16% eram tabagistas e 36% eram etilistas. No entanto, o Teste Qui-quadrado não apresentou significância estatística entre gêneros, hábitos de vida e graus de acometimento. Conclusão: O estudo demonstrou alta prevalência de sintomatologias de DTM em indivíduos com disfunções cervicais. As evidências apresentadas servem como ponto de partida para incentivar novas pesquisas sobre o assunto, oferecendo subsídios de conhecimento epidemiológico. [resumo fornecido pelos autores]
Keywords: Fisioterapia; Articulação temporomandibular; Coluna cervical - Doenças